Kualitas Pelayanan Agen Gas 3 Kg Bersubsidi PT. Vistagas Di Kelurahan Tondo Kota Palu - Adiputra, Rahmat; Daswati; Erdyansyah (JPS: Journal of Publicness Studies, 2025)
Tondo Sub-district faces various challenges in the distribution of subsidized gas managed by PT. Vistagas agents, where several technical and administrative obstacles affect the quality of services received by distribution bases as partner outlets. This study aims to analyze the quality of services provided by the subsidized gas agent PT. Vistagas in Tondo Sub-district, Palu City. The main focus of this research is to determine the extent to which the services provided have met the expectations of distribution bases as the recipients. This study uses a qualitative approach with a descriptive type, and data collection was carried out through observation, in-depth interviews, and documentation. The results of the study show that although gas distribution generally runs regularly and on schedule, several issues remain, such as uncertainty in delivery times, lack of price transparency, and limited communication from the agent to the distribution bases. The service is considered suboptimal due to mismatches between the needs of the bases and the services provided, including in terms of timeliness, clarity of information, and service attitude. These shortcomings influence the perception and satisfaction level of the bases toward the agent's performance. This study recommends that PT. Vistagas improve its distribution system, clarify information regarding quotas and delivery schedules, and strengthen communication with the distribution bases to create a more efficient, fair, and community-responsive service.